2009
DOI: 10.5194/acpd-9-15769-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of black carbon estimations in global aerosol models

Abstract: Abstract. We evaluate black carbon (BC) model predictions from the AeroCom model intercomparison project by considering the diversity among year 2000 model simulations and comparing model predictions with available measurements. These model-measurement intercomparisons include BC surface and aircraft concentrations, aerosol absorption optical depth (AAOD) from AERONET and Ozone Monitoring Instrument (OMI) retrievals and BC column estimations based on AERONET. In regions other than Asia, most models are biased … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
308
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 170 publications
(326 citation statements)
references
References 115 publications
(58 reference statements)
17
308
1
Order By: Relevance
“…Additionally we have included two sensitivity simulations that have the in-cloud impaction processes turned off for both the diagnostic and prognostic in-cloud scavenging schemes, DIAG-FULL-noimp and PROG-AP-noimp, respectively. Figure 14 shows profiles from the tropics and midlatitudes taken between the equator, and 50 • N and between 120 • E and 60 • E and averaged for the same points as shown in Koch et al ( , 2010. Figure 15 presents profiles from the high latitudes taken between 50 • N and 80 • N and between 180 • E and 60 • E and averaged for the same points as shown in Koch et al ( , 2010.…”
Section: Comparison With Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally we have included two sensitivity simulations that have the in-cloud impaction processes turned off for both the diagnostic and prognostic in-cloud scavenging schemes, DIAG-FULL-noimp and PROG-AP-noimp, respectively. Figure 14 shows profiles from the tropics and midlatitudes taken between the equator, and 50 • N and between 120 • E and 60 • E and averaged for the same points as shown in Koch et al ( , 2010. Figure 15 presents profiles from the high latitudes taken between 50 • N and 80 • N and between 180 • E and 60 • E and averaged for the same points as shown in Koch et al ( , 2010.…”
Section: Comparison With Observationsmentioning
confidence: 99%
“…Figure 14 shows profiles from the tropics and midlatitudes taken between the equator, and 50 • N and between 120 • E and 60 • E and averaged for the same points as shown in Koch et al ( , 2010. Figure 15 presents profiles from the high latitudes taken between 50 • N and 80 • N and between 180 • E and 60 • E and averaged for the same points as shown in Koch et al ( , 2010. These figures show that the predicted black carbon profiles, particularly in the middle troposphere differ from the observations, and between each other, by up to two orders of magnitude depending on the treatment of in-cloud scavenging.…”
Section: Comparison With Observationsmentioning
confidence: 99%
“…While ACCMIP includes data from the Global Fire Emission Database 2 (GFED2), we also explore ACCMIP emissions using the more recent GFED3 monthly biomass burning emission database (van der Werf et al, 2010) and we allow these emissions (sulfur, black carbon and organic matter) to vary annually instead of using a climatological mean. Koch and Hansen (2005) showed that, while the largest contribution in terms of sulfate aerosols to Arctic AOD comes from Russia, South-East Asia contributes with a significant fraction. Since there is a significant difference in terms of sulfate emissions between the REAS and AC-CMIP emission datasets, we explore the possible impact of a change in anthropogenic SO 2 emissions in the SouthEast Asia region.…”
Section: Echam5-ham and Emissionsmentioning
confidence: 99%
“…(Law and Stohl, 2007;Stohl, 2006;Stocks et al, 1998;Koch and Hansen, 2005), with important interannual variability, the choice of biomass burning emissions datasets may play an important role. Variability in these emissions, interacting with interannual changes in circulation, may lead to significant changes in Arctic aerosol concentrations.…”
Section: Echam5-ham and Emissionsmentioning
confidence: 99%
See 1 more Smart Citation